2020
DOI: 10.3390/ijerph17238748
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Kaizen Event in a Sterile Processing Department of a Rural Hospital: A Case Study

Abstract: Operating Rooms (ORs) generate the largest revenues and losses in a hospital. Without the prompt supply of sterile surgical trays from the Sterile Processing Department (SPD), the OR would not be able to perform surgeries to its busy schedule. Nevertheless, little emphasis has been brought in the medical literature to research on surgical instrument processing in the medical literature. The present study was done applies an Enhanced Kaizen Event (EKE) in the SPD of a rural hospital to identify sources of waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
2
20
0
2
Order By: Relevance
“…Strategies such as empowerment, engagement, and leadership directly from the aides and nurses in discussion sections and, more importantly, in the decision-making process allowed the team to get into the implementation face and the project's success. The involvement of such stakeholders makes the difference between a success or a failure in the trajectory of a Lean or Kaizen project in the healthcare sector (Lindsay, Kumar & Juleff, 2020;Nino, Claudio, Valladares & Harris, 2020) One phrase that can be heard about healthcare is that standardization and standardized work are hard to implement because "every patient is different." There is no way to predict what can happen or be able to make every process the same.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies such as empowerment, engagement, and leadership directly from the aides and nurses in discussion sections and, more importantly, in the decision-making process allowed the team to get into the implementation face and the project's success. The involvement of such stakeholders makes the difference between a success or a failure in the trajectory of a Lean or Kaizen project in the healthcare sector (Lindsay, Kumar & Juleff, 2020;Nino, Claudio, Valladares & Harris, 2020) One phrase that can be heard about healthcare is that standardization and standardized work are hard to implement because "every patient is different." There is no way to predict what can happen or be able to make every process the same.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges that many teams have faced when applying lean tools in healthcare facilities is getting much-needed support and engagement from principal stakeholders such as medical professionals and administrators. The involvement of stakeholders could make the difference between a success or a failure in the trajectory of a lean project in the healthcare sector (Lindsay, Kumar & Juleff, 2020;Nino, Claudio, Valladares & Harris, 2020). In this study, the engineering team worked closely with administrators at the healthcare facility letting them know that their leadership and support made the difference in having impactful outcomes and reaching sustainability of the changes and improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research [ 9 , 10 , 11 , 12 , 13 ] highlighted the Lean philosophy as a strategy allowing companies in any sector to adapt to rapid changes in the market, in the economy, in technical and social complexity issues, and in the needs of customers as well as for the health sector to adapt to the demands discussed above. A bibliographic review found great diversity, for example, in the area of emergency care, one of the most complex and haphazard areas [ 12 , 13 , 14 , 15 , 16 ] where this philosophy was applied for process improvement with successful results. Other researchers, such as Guzmán [ 6 ], also showed how, in the last 10 years, general hospital departments published results of process improvement and time optimization in emergency medicine, surgery, pharmacy, nursing, oncology, and administration reflecting the success of having implemented the Lean philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review indicated health systems more and more worked to implement these changes. Recent research [9][10][11][12][13] highlighted the Lean philosophy as a strategy allowing companies in any sector to adapt to rapid changes in the market, in the economy, in technical and social complexity issues, and in the needs of customers as well as for the health sector to adapt to the demands discussed above. A bibliographic review found great diversity, for example, in the area of emergency care, one of the most complex and haphazard areas [12][13][14][15][16] where this philosophy was applied for process improvement with successful results.…”
mentioning
confidence: 99%